SISTEM PENJADWALAN MATA PELAJARAN PADA SMK XY DENGAN ALGORITMA GENETIKA - Achmad Noe’man; Tyastuti Sri Lestari; Ajif Yunizar Pramata Yusuf (JURNAL MITRA MANAJEMEN, 2022)
Scheduling is a process of compiling and making teaching and learning schedules which are carried out repeatedly every one semester. The goal to be achieved in this research activity is to obtain various materials needed for making subject scheduling applications, including being able to design a subject scheduling system that can meet the learning needs of schools and can find out the benefits of implementing the scheduling information system for SMK XY. In this study, an information system for scheduling subjects was made that would help SMK XY in managing the schedule of subjects more effectively and efficiently. The method used in this study uses the Genetic Algorithm method. Genetic Algorithm that runs by utilizing a scientific selection process known as the evaluation process, so that it can be used to generate scheduling according to existing data. The final result of the subject scheduling information system using genetic algorithms, namely the schedule of subjects at SMK XY can be obtained faster because there is already a genetic algorithm calculation in the scheduling system, so that it can be optimal in scheduling subjects at SMK XY. Keywords : Scheduling; Genetic Algorithm;